Determinant Of Corporate Social Responsibility And Its Implication Of Financial Performance - Hamdani; Dhea Zatira; Eni Suharti (Jurnal Akuntansi, 2022)
This study aims to see whether green accounting, environmental performance and company size can affect company performance moderated by CSR for the 2016-2020 period. This study uses a panel data regression method with a sample of companies listed in PRPOPER. The results show that partially green accounting and environmental performance variables can affect companies in implementing CSR while the size variable can not have an effect, as well as in the next results only environmental performance variables that can affect financial performance while green accounting, size and CSR have no effect on financial performance. An interesting finding is that green accounting which is a cost that must be incurred for CSR activities does not affect financial performance where this indicates that companies that implement CSR consider that environmental costs have been treated as operating costs in general.